Fatores econ??micos e sociais: impacto no resultado do ??ndice de Desenvolvimento da Educa????o B??sica (IDEB) de munic??pios do Estado de S??o Paulo de 2005 a 2015 - Silva, Carlos Daniel da (2017)
This study, developed under the Stricto Sensu Post Graduation Program in Education at Universidade Cat??lica de Bras??lia (UCB), discusses the influence of economic and social variables on the results of the Basic Education Development Index (Ideb), in Municipalities of the State of S??o Paulo, from 2005 to 2015. In order to analyze such influences, It has been studied the issue of Brazilian federalism and its historical implications, especially economic and social inequality in Brazil and the State of S??o Paulo. A bibliographical research was also carried out with the purpose of analyzing the state of the art of inequality and its implications in education, as well as the financing of education in Brazil. In order to give more support to the research, an exploratory research was also carried out, with an analysis of numerous financial documents of municipal expenditures, historical expenditure series on education, health and sanitation, besides tax collection, Gini index, Social Vulnerability Index of the State of S??o Paulo, average income of families, population and data of all editions of Ideb. As a type of research the quantitative data analysis was used in panel, in which it was sought to verify the influence of the economic and social variables in the variation of the Ideb over time. The panel analysis identified that the variables education expenditure, teacher compensation, sanitation, Tax on Operations Related to the Circulation of Goods and on Services of Interstate, Intermunicipal and Communication Services (ICMS) share has an influence on Ideb's result, although it does not explain the total results of the indicator. Research shows that extra classroom factors, of a social nature, can make a difference in improving the quality of education, when considering the ideb indicator.